Entamoeba ranarum Infection in a Ball Python (Python regius). (August 2020) - Michaely, L.M.; von Dörnberg, K.; Molnár, V.; Tappe, D.; Tannich, E.; Hewicker-Trautwein, M.; Wohlsein, P.
Summary: The pathogenic Entamoeba species in snakes is widely regarded to be Entamoeba invadens, which can cause severe amoebiasis with up to 100% mortality. In this case report, we describe a ball python ( Python regius ) that died after short-term weight loss. Necropsy revealed severe necrotizing colitis with large numbers of intralesional Entamoeba trophozoites. Molecular genetic analysis identified these trophozoites as Entamoeba ranarum, a parasite more usually found in amphibians. Furthermore, the extended history revealed that toads ( Rhinella marina ) had been housed together with the python. This report illustrates the danger of protozoal cross-infections in exotic animals as well as the importance of molecular genetic tools in Entamoeba diagnosis.